Analysis of off-the-wall smash shots in men`s and women`s professional padel - Martín-Miguel, I.; Muñoz, D.; Escudero-Tena, A.; Sánchez-Alcaraz, B. J. (Perceptual and Motor Skills, 2024)
Purpose: our aim was to analyze the characteristics of the off-the-wall smash in men´s and women´s padel, and to compare gender differences in the set-dependent frequency of these shots.